Fragility Comprehensive Assessment of Low-Rise Cold-Formed Steel Framed Wall Structure Subjected to Wind Load - Hao Zhang; Shiwei Hou; Yiming Ding; Chao Li; Pengfei Liu (Shock and Vibration)
This paper presents a comprehensive assessment method of the fragility of low-rise cold-formed steel (CFS) framed wall structures subjected to wind hazards considering the fragility of both the main structure and the cladding system. The effects of wind directions on the fragility of CFS framed wall structures were also studied. For the main structure, the fragility curve is established using the maximum interstory drift ratio (ISDRmax) as the performance index for assessing the wind fragility of the structure. For the cladding system, the probabilistic models of the wind load and the cladding component resistance are established based on Monte Carlo simulation, and then methods for the fragility assessment of single cladding components and the cladding system under wind hazards considering the influence of the number and arrangement of the cladding components are proposed. The results indicated that, under strong wind, the cladding system may be damaged before the required wind resistance capacity of the main structure is exhausted. In particular, the roof sheathing is the most prone to damage, followed by the stud wall. That is, before the main structure is severely damaged or collapses, the cladding systems may be severely damaged, rendering the structure unusable. Therefore, the comprehensive assessment of the fragility of this type of structure subjected to wind hazard considering the fragility of both the main structure and the cladding system is more accurate. This study is of great significance for the improvement of the wind resistance performance of CFS structures and the popularization of this type of structure.